The effect of hub design on lower limb muscle activation while riding on different terrain - Tsai, W.-C.; Shao, T.-F.; Lee, Y.-S.; Chen, C.-H. (Journal of Science and Cycling, 2019)
Background: In cycling, bike wheels are the direct bike-to-ground object that plays one of the most important roles that keeps the bike moving. However, in all structures that make up a wheel, hub stands the most important part. Yet, whether different hub design would influence lower limb muscle activation or not is currently uncertain.